Advances in the bonded composite repair of metallic aircraft structure - Baker, A. A. (Alan A.); Rose, L. R. F.; Jones, R. (Rhys) (Amsterdam ; Boston : Elsevier, 2002)
The availability of efficient and cost-effective technologies to repair or extend the life of aging military airframes is becoming a critical requirement in most countries around the world, as new aircraft becoming prohibitively expensive and defence budgets shrink. To a lesser extent a similar situation is arising with civil aircraft, with falling revenues and the high cost of replacement aircraft. This book looks at repair/reinforcement technology, which is based on the use of adhesively bonded fibre composite patches or doublers and can provide cost-effective life extension in many situations. From the scientific and engineering viewpoint, whilst simple in concept, this technology can be quite challenging particularly when used to repair primary structure. This is due to it being based on interrelated inputs from the fields of aircraft design, solid mechanics, fibre composites, structural adhesive bonding, fracture mechanics and metal fatigue. The technologies of non-destructive inspection (NDI) and, more recently smart materials, are also included. Operational issues are equally critical, including airworthiness certification, application technology (including health and safety issues), and training. Including contributions from leading experts in Canada, UK, USA and Australia, this book discusses most of these issues and the latest developments. Most importantly, it contains real histories of application of this technology to both military and civil aircraft.
Introduction. Materials and processes. Design procedures. Experimental patching studies. Certification issues. Application considerations. Recent applications and demonstrators.
Includes bibliographical references and index.
Keywords: Airplanes -- Maintenance and repair -- Materials; Airframes -- Maintenance and repair; Adhesives; Metal bonding; Composite materials -- Bonding; Electronic books